Využití viskoelastických metod v chirurgii - Šmíd, D; Zatloukal, J; Kural, T; Fichtl, J; Opatrný, V; Moláček, J (Rozhledy v chirurgii, 2018)
INTRODUCTION: Major liver resections are associated with high morbidity and mortality. The main causes of this fact include a significant blood loss which may be associated with this surgical procedure. Hemocoagulation disorder, diagnosed by standard laboratory tests, is very frequent in the postoperative period and often requires the administration of blood derivatives. Several recent studies, however, have questioned the presence of such coagulopathy when viscoelastic methods are used to assess the coagulation process. The studies have concluded that that the coagulation disorder only exists at a laboratory level, the coagulation process itself being unaffected, and no therapeutic intervention is therefore needed. The use of viscoelastic methods may play a crucial role in deciding whether or not to correct the assumed coagulation disorder. METHOD: Our study was designed as a prospective observational study. Data were collected in the Surgical Intensive Care Unit during one year (1 January - 31 December 2016). The study included 18 patients who underwent major liver resection. When coagulation disorder was diagnosed using standard coagulation tests in the postoperative period, we performed a ROTEM examination. The results of the standard and ROTEM examination were then compared. RESULTS: Out of the total of 18 patients enrolled in the study, a coagulopathy was diagnosed in 15 cases (83%) using standard coagulation tests. In these patients, we performed rotational tromboelastometry (ROTEM) which did not show any coagulation disorder. CONCLUSION: Our study has demonstrated that when viscoelastic methods are used to evaluate the function of blood clotting in patients after major hepatic surgery, no coagulopathy has been found as opposed to the evaluation with standard blood clotting tests. Unnecessary transfusions of blood derivatives can be avoided as well as all risks linked to their administration. Viscoelastic methods of coagulation assessment (ROTEM, TEG) help provide a detailed insight into the coagulation process and our observations have shown that they should play a significant role in the postoperative assessment of patients following major hepatic resections.Key words: ROTEM - viscoelastic methods - coagulopathy.
Keywords: Hemorrhage; krvácení; Blood Coagulation Disorders; koagulopatie; Blood Coagulation Tests; tromboelastografie; Liver Diseases; lidé; Prospective Studies; Thrombelastography; vyšetření krevní srážlivosti; Humans; nemoci jater; prospektivní studie